Bimetallic NiCo2O4 catalyst application for hydrogen generation via ethanol steam reforming - Ashutosh K.; Ram P.; Chandra S.Y. (My University, 2025)
Ethanol steam reforming (ESR) is one of the sustainable options for renewable hydrogen generation. In this study Co, Ni and their bimetallic spinel (NiCo2O4) were studied for ESR performance. The prepared catalyst was characterized with surface area analyser, XRD, XPS and SEM. The ethanol and water mixture were taken in stoichiometric condition and reaction was performed from 573K to 823K at interval of 50K. The NiCo2O4 catalyst has shown completion of ethanol conversion with higher hydrogen selectivity (62%) comparative to Ni and Co at 773K. The product gas distribution in outlet gas found that dehydrogenation, hydrogenolysis and decomposition of ethanol are most favoured reactions during ESR. © 2018 World Research Association. All rights reserved.